Konstruksi Identitas Anak Pekerja Migran Indonesia yang Ditinggalkan (Studi Kasus Anak Motherless Di Desa Sambirejo, Kecamatan Jumantono, Kabupaten Karanganyar, Jawa Tengah) - Akbar Syafa Nugraha (Journal of Development and Social Change, 2025)
This study aims to explore the process of identity construction of abandoned children of Indonesian migrant workers, especially children whose mothers work abroad (motherless), the socialization they go through, and the challenges and problems they face in constructing their identity in Sambirejo Village, Karanganyar Regency, Central Java. Using a qualitative approach and case study method, this research will explore how these children construct and interpret their self-identity and social identity in the context of mother absence. The main focus of the research is on the children's subjective experiences, the socialization process, the challenges faced, the adaptation strategies they develop. Five children of migrant workers are the key informants in this study, while the supporting informants are grandmothers, aunts, and siblings who take care of them at home. Data will be collected through in-depth interviews, participant observation, and document analysis. The results show that the children of migrant workers left behind in Sambirejo Village form their self-identity and social identity through three stages in Richard Jenkins' Social Identity theory, namely individual order, interaction order, and institutional order. It is hoped that the results of this study can provide a deeper understanding of the impact of labor migration on the construction of the identity of children left behind, as well as the basis for developing more effective policies and support programs for children of migrant workers in developing themselves and their identities so as not to lead to deviant behavior.